Sumpah dan Perkembangan Emosi Anak Usia 4-6 Tahun: Studi Etnografi - Purnama, Sigit; Indriani, Yuli Rahayu; Abdul Latif, Muhammad; Sugeng Desyanty, Ellyn (Universitas Pendidikan Ganesha, 2022)
Misuh (swearing) is one of the identities of people in the world in general. Misuh culture is not only practiced by adults but also by children. This ethnographic study aims to explore the impact of misuh (swearing) culture on children's emotional development with parents who work as TKW (female workers). The research method uses a type of qualitative research with an ethnographic approach. The research subjects were 5 children who had the intensity of saying the word misuh most often in South Malang. Collecting research data by observation, interviews and documentation. Data analysis was performed using code-based analysis and case-based analysis in Qualitative Data-Mining (QDM) at Child Welfare (CW). The results showed that the misuh words uttered by the participants were jancuk, bedhes, asu, kirek, taek, gendeng, kontol, and patek. Semantically, these words are a harsh and taboo language for the speech tradition. However, the purpose of using these words has different meanings depending on the speaker's context. The use of the misuh words (swear words) spoken by the participants can express the meaning of annoyance, cursing, greetings, patience, intimacy, strength, jokes, ridicule, and admiration. The purpose of these words is the expressions of both positive and negative emotions. Most of the participants showed more negative emotional expressions. This finding has implications for the emotional development of children.